Culture of human dental pulp cells at variable times post-tooth extraction - BENÍCIO Daniela Ferreira Araújo; PEREIRA Luciana Oliveira; SILVA Izabel Cristina Rodrigues da; AZEVEDO Ricardo Bentes; BEZERRA Ana Cristina Barreto (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study was to investigate the viability of human dental pulp cells from extracted teeth kept at standard room temperature and atmospheric pressure for different periods of time. Twenty-one healthy permanent teeth were used. They were divided into five groups according to the expected time from extraction to processing. One group was tested immediately after extraction; the other groups were each tested at one of the following time points: 30 minutes, 1 hour, 2 hours, and 5 hours post-extraction. Cell morphology was analysed by light microscopy; cell proliferation was analysed using MTT assay and by counting the viable cells in a haemocytometer. Similar results were observed in all groups (p < 0.05). A delay of up to five hours for tooth processing and tissue collection does not preclude the establishment of dental pulp cell cultures, affect the morphology of these cells, or reduce their proliferative potential.